2015
DOI: 10.3892/mmr.2015.4171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcatheter arterial chemoembolization on cellular immune function and regulatory T cells in patients with hepatocellular carcinoma

Abstract: The present study aimed to investigate changes in cellular immune function and regulatory T cells (Tregs) in patients with hepatocellular carcinoma (HCC) prior to and following transcatheter arterial chemoembolization (TACE) and their clinical significance. The proportion of CD4+ and CD8+ T cells and Tregs in the peripheral blood between healthy volunteers and patients with HCC were detected by flow cytometry prior to (1 day) and one month following TACE. The level of interleukin (IL)‑35 in the peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 24 publications
2
53
0
Order By: Relevance
“…29 This capacity for immune potentiation was recently demonstrated in an Asian study, 30 in which TACE significantly decreased the percentage of circulating CD4 + CD25 + regulatory T cells (Treg) in HCC patients. These Treg cells, in turn, are major negative regulators of tumor immunity suppressing the production of immune cytokines, such as IFN-g, from tumor-specific cytotoxic T cells.…”
Section: Discussionmentioning
confidence: 92%
“…29 This capacity for immune potentiation was recently demonstrated in an Asian study, 30 in which TACE significantly decreased the percentage of circulating CD4 + CD25 + regulatory T cells (Treg) in HCC patients. These Treg cells, in turn, are major negative regulators of tumor immunity suppressing the production of immune cytokines, such as IFN-g, from tumor-specific cytotoxic T cells.…”
Section: Discussionmentioning
confidence: 92%
“…It has been shown that the necrosis and ischemia caused by TACE initially induce the production of acute phase cytokines such as interleukin (IL)-6 and IL-22, while in later phases immunosuppressive cytokines such as IL-10 are increased [29]. Moreover, a decrease of T regulatory (T reg) cells has been observed following TACE, indicating the restoration of immune function after treatment [30]. In our study, TACE induced a significant raise of sTIM-3 levels at the first week post-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that chemotherapy may result in immunomodulation in patients, suppressing the inhibitory immune cell function. Cellular immunity serves a key role in the antitumor immune response (23). T cells are critical in the immune regulation and surveillance involved in cellular immunity, and are divided into two major subsets: CD4 + and CD8 + .…”
Section: Discussionmentioning
confidence: 99%